Manenberg negotiated: answering questions communities are not asking - Hedley, Phillippa (School of Architecture, Planning and Geomatics, 2024)
Within the global South, the public realm is often characterised as a territory of intense accessibility and spatial claims, equally enabling and constricting citizens to shape and reshape an inclusive place within the informal city. The contemporary African city has been central to the discourse around the rapidity of urban development and influx, producing a global narrative of the inability of a frail postcolonial metropolis to support this growth. What is emerging, however, is the resulting improvisation of the city's inhabitants to reimagine their contrasting, everyday environments for the city's negotiation and daily navigation. Often, the global discourse omits the finer, more nuanced informality of life that the African city's marginalised users employ in the everyday to innovatively sustain their livelihood. Central to this imagination, is the Designer's role to spatially represent all citizens within the urban arena; achieving this through the People's City design approach. This participatory, incremental approach produces innovation outside the preconceived idea of a design product; rather, pursuing the process over the product. If more than half the city is marginal, the role facing practice should be framing solutions from the perspective and design of citizen/community majority. As Hamdi observes, the integrity of developing an inclusive approach in design, is through the collective voice and experience from within the community context itself; “practice, then, is about making the ordinary special and the special more widely accessible - expanding the boundaries of understanding and possibility with vision and common sense... It is about getting it right for now and at the same time being tactical and strategic about later” (Hamdi, 2004). Manenberg, Cape Town, provides insight into the negotiation of community spaces; where form-making operates outside of the regular and explores how previous areas of exclusion contribute to an emergence of a more flexible and adaptable city. Rather than the static public realm, Manenberg demonstrates “a temporal articulation and occupation of space which not only creates a richer sensibility of spatial occupation, but also suggests how spatial limits are expanded to include formally unimagined uses in dense urban conditions” (Mehrotra, 2010). These unimagined, informal spatial nuances become the co-construction of choice and improvisation that composes daily life. This collaboration and co-constructing of place formed the catalyst from which the research project pursues the process over the product, and was the key in developing an action research methodology to partnering and co-design with community members. The overarching thread that this research project attempts to explore in its approach, is: how can designers intervene in a manner which creatively alters the persistent dominance of exclusion in the public realm? And, in doing so, can the community be invited into the process? Throughout this iterative design, three principles emerged: People, power and place; through these the design process could be interrogated across multiple scales, with participants establishing outcomes, diagnosing spatial negotiations and dreaming proposed interventions. The co-design process in the research project required active engagement, where the participants explored values, issues, threats and opportunities relating to the principles through a series of three process stages: Diagnosis, Dreaming and Designing. The intention was to allow the question of what the community wanted to emerge from within the groups. This process framework provides an opportunity for the group members to revisit their visioning iteratively during each process stage, testing and negotiating decisions of how interventions can be achieved. It allows the participants a space to comprehend urban solutions and explore alternatives, responding to on-the-ground issues from local and nuanced experience. Answering questions communities are not asking: this subtitle becomes a commentary, or perhaps a statement, on how previous areas of exclusion, the marginalised and the informal city, often do not have a voice in the conversation of how their spaces are conceived and designed for them, without them. The research project concludes with strategies of intervention, with outcomes and solutions generated from the process of co-design. These strategies were then transposed into incremental interventions, testing the greatest impact to alter the accessibility of the public realm. The greatest tool to emerge from the community-led approach was the identification of potential partnerships which strengthened the dynamics in negotiating the public realm; illustrating that if communities are offered a seat at the table, the designs become all the richer, participating in the emergence of a more flexible, incremental and adaptable city.